Digital Natives, Critical Strangers: The Challenge of Student Critical Literacy in Indonesia's Post-Truth Era - Fitriani, Nining; Aqham, Ahmad Ashifuddin; Wahid, Kholid; Muin, Abdul (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
In the post-truth era, where emotional narratives often overshadow facts, digital natives encounter increasing challenges in identifying credible information. This study examines the critical digital literacy of Indonesian university students, focusing on their habits and perceptions in verifying information from online sources. Using a qualitative descriptive method, data were collected from eight students through semi-structured interviews, observational notes, and open-ended questionnaires, and then analyzed thematically. The findings reveal that 75 percent of participants admitted to having believed hoaxes at least once, while only 3 out of 8 consistently verify content before sharing. Platforms such as TikTok and Instagram were the most frequently used sources of information. Trust was often based on virality, familiarity, or emotional appeal rather than the credibility of the source. Some respondents viewed truth as what is widely accepted or repeated within their social circles. Notably, those who had personal experiences with misinformation developed a stronger awareness of the need for fact-checking. This study highlights a paradox between students’ digital skills and their critical literacy. It suggests that epistemic authority is shifting from academic or institutional sources to influencers and peer networks. The research calls for higher education curricula to incorporate critical digital literacy that combines technical ability, ethical reasoning, and emotional awareness. Such integration is vital for preparing students to navigate a complex and often misleading information landscape.